Adverse Event Management in Patients with BRAF V600E‐Mutant Non‐Small Cell Lung Cancer Treated with Dabrafenib plus Trametinib. (31st December 2018) - Chalmers, Anna; Cannon, Laura; Akerley, Wallace
Abstract: : Therapies for advanced non‐small cell lung cancer (NSCLC) continue to become more sophisticated. Chemotherapeutics are giving way to newer approaches such as immune checkpoint inhibitors and targeted therapies for greater efficacy and improved outcomes. Dabrafenib plus trametinib combination therapy was first approved for the treatment of metastatic melanoma harboring the BRAF V600‐mutation in 2014. In 2017, the U.S. Food and Drug Administration approved the combination for patients with NSCLC with the same mutation based on an ≈ 65% response rate and median progression‐free survival of 10–11 months. BRAF mutations are a high‐frequency event in melanoma (≈ 50%), whereas the overall incidence in lung cancer is ≈ 2%, but similar in number, because of the high incidence of the disease. As a new approach in NSCLC treatment, dabrafenib plus trametinib has a unique toxicity profile that is likely unfamiliar to care providers in thoracic and general oncology who have not used the combination to treat patients with melanoma. Common adverse events such as pyrexia, fatigue, and nausea, as well as a range of less frequent cutaneous, ocular, and hemorrhagic events, can be observed during treatment with dabrafenib plus trametinib. Previous experience in metastatic melanoma revealed that these events can be effectively managed to improve patient quality of life and reduce unnecessary drug discontinuation. The aim of this review is to summarize treatment guidelines, along with key insights obtained from previous clinical‐trial and real‐world experience in patients with metastatic melanoma, to properly manage toxicities associated with dabrafenib plus trametinib for NSCLC. Abstract : The review summarizes treatment guidelines, along with key insights obtained from previous clinical‐trial and real‐world experiences in patients with metastatic melanoma, to properly manage toxicities associated with dabrafenib plus trametinib for non‐small cell lung cancer.